Track the dynamical features for mutant variants of COVID-19 in the UK - Ray-Ming Chen (Mathematical Biosciences and Engineering, 2021)
Aims: The main purpose of this study is to explore whether the new variant SARS-CoV-2 VOC 202012/01 in the UK is equipped with some leading or underlying features.